Path Analysis on the Determinants of Unwanted Pregnancy Among Adolescents in Madiun, East Java - Mutiara, Bunga; Budihastuti, Uki Retno; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2018)
Background: Unintended pregnancy is a worldwide problem that affects women, their families, and society. Unintended pregnancy can result from early marriage, contraceptive failure, non-use of contraceptive services, and, less commonly, rape. Consequences of unintended pregnancy include